O18.1 Prevalence of active syphilis among transwomen in são paulo, brazil. (14th July 2019) - Paiatto, Beatriz; Farland, Willi Mac; Veras, Maria; Lin, Jess; Wilson, Erin; Turner, Caitlin; Oliveira, Elaine; Silveira, Edilene; Silveira, Paula; Junior, José; Barros, Claudia
Abstract : Background: Studies document that transwomen bear one of the most severe burdens of HIV worldwide, yet little information is available on the prevalence of other sexually transmitted infections (STI). Of particular concern in Brazil is the lack of data on the prevalence of syphilis specifically for transwomen in a background of increasing syphilis diagnoses among other populations. The aim of the present analysis was to estimate the prevalence of active syphilis infection among transwomen in a large, community-based sample from São Paulo, Brazil. Methods: We analyzed baseline data from the Trans*National Study, a cohort being assembled to longitudinally track health issues among transwomen in São Paulo, Brazil. Participantswere recruited using respondent-driven sampling (RDS), a long-chain peer-referral methodology to obtain population-based data from hard-to-reach communities. Participants completed a structured questionnaire, HIV testing, antibody tests for Treponema pallidum, and, if positive, Venereal Disease Research Laboratory (VDRL) test titers. Active syphilis was defined as a positive treponemal-specific antibody test plus a VDRL titer greater than 1:8, consistent with national treatment guidelines. Results: Of 729 transwomen interviewed, 32.1% were 24 years of age or younger and 75.6% earned under the city's minimum wage. A majority (453/729, 62.1%) tested antibody-positive for syphilis. Among those, the VDRL titer was greater than 1:8 for 37.5% (170/453), suggesting a point prevalence of active syphilis of 23.3% (95% CI 20.3–26.6) in the population. Of those with evidence of active syphilis, only 35.3% (60/170) reported ever having a syphilis test. HIV prevalence was 28.7% in the sample; 70 transwomen were living with HIV and had evidence of active syphilis (overall co-infection 9.6%). Conclusion: Our community-based sample in São Paulo, Brazil suggests one-fifth to one-fourth of transwomen have active syphilis, with possibly most going untreated. This study highlights the urgent need for screening and prevention strategies for STI infection, especially syphilis, for transwomen. Disclosure: No significant relationships.